2019
DOI: 10.1039/c9ra06153c
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed GaOOH rods loaded on the surface of ZnBiNbO5particles with enhanced photocatalytic activity toward enrofloxacin

Abstract: A GaOOH/ZnBiNbO5 composite was constructed by loading dispersed GaOOH rods on the surface of ZnBiNbO5 particles and characterizations, including SEM-EDS, XRD, FT-IR spectroscopy, XPS, and UV-Vis DRS were performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…With increasing the ball milling time, the absorption in the shorter wavelength region (under 220 nm) characteristic of GaOOH became appreciable, while the absorption in the longer wave region given by b-Ga 2 O 3 having a narrower band gap than GaOOH decreased. 23 Thus, from the XRD and UV-vis results, it can be concluded that Ga UV-Vis spectra for the calcined samples are compared in Fig. 3(B).…”
Section: Photocatalytic Reduction Of Co 2 With Watermentioning
confidence: 99%
“…With increasing the ball milling time, the absorption in the shorter wavelength region (under 220 nm) characteristic of GaOOH became appreciable, while the absorption in the longer wave region given by b-Ga 2 O 3 having a narrower band gap than GaOOH decreased. 23 Thus, from the XRD and UV-vis results, it can be concluded that Ga UV-Vis spectra for the calcined samples are compared in Fig. 3(B).…”
Section: Photocatalytic Reduction Of Co 2 With Watermentioning
confidence: 99%
“…Al-O and Ga-O bonds show the similar positions at ∼531.5 eV[25- 27]. The peak at 532.6 eV mainly corresponds to OH bonds in Al doped α-GaOOH and from surface-adsorbed hydroxides[27][28][29]. Besides, O 2 in oxygen-deficient regions at room temperature also partly contributes to the high-energy peak[19,24,30].…”
mentioning
confidence: 99%